Percepción y temporalidad: Husserl frente a Heidegger - García, José Luis (Pontificia Universidad Católica del Perú, 2024)
This contribution is part of a copious bibliographic tradition that has sought the points of encounter and disencounter between the two most relevant phenomenologists of the 20th century: Husserl and Heidegger. Starting from the critical foundations of the 1919 public emergence of Heidegger’s project of an originary science, I propose, first of all, to review his criticism of the history of philosophy, which, in his opinion, has committed the original sin of being theoretical. And along these lines, I also review how this theorization has been mainly seen in the absolutization of perception when describing the original relationship between human beings and the world. This critical thread, though not explicit, reaches into Husserl’s quarries. Faced with this, secondly, I attempt a possible response to said critique in light of Husserl’s discovery of the absolute flow of consciousness as found in his Lectures on the Internal Time Consciousness.

Este texto se inscribe en una copiosa tradición bibliográfica que ha buscado los puntos de encuentro y desencuentro entre las figuras fenomenológicas más importantes del siglo XX: Husserl y Heidegger. De esta forma, y partiendo de las bases crítica que supone la irrupción pública del proyecto de la ciencia originaria heideggeriana en 1919, me propongo, en primer lugar, repasar la crítica de Heidegger a la historia de la filosofía, la cual, a su juicio, ha cometido el pecado original de ser teórica; y, en esa línea, cómo dicha teorización se ha visto, principalmente, en la absolutización de la percepción al momento de describir la relación originaria entre el ser humano y el mundo. Este hilo crítico, aunque no sea explícito, llega hasta las canteras de Husserl. Frente a esto, en segundo lugar, ensayo una posible respuesta a dicha crítica a la luz del descubrimiento husserliano del flujo absoluto, el cual podemos extraer de las Lecciones sobre la conciencia interna del tiempo.
Keywords: Husserl; Heidegger; Perception; Temporality; Absolute flow; Husserl; Heidegger; Percepción; Temporalidad; Flujo absoluto; https://purl.org/pe-repo/ocde/ford#6.03.01